Land Suitability and Plant Types Based on Soil Electrical Properties and Remote Sensing - Eleonora Agustine; Nadhira Gunawan; Rifky Nauval; Muhammad Abdilllah Budianto; Irwan Ary Darmawan; Dini Fitriani; Kartika Hajar Kirana; Wahyu Srigutomo; Asep Harja; Imran Hilman Mohammad; Eddy Supriyana (Jurnal Geologi dan Sumberdaya Mineral, 2023)
Regional development in Panimbang District, Banten Province, Indonesia, is executed so that the tourism area is not centered solely on the west coast of Pandeglang but also in the surrounding area. The development is carried out in stages from government offices, education facilities, and public facilities. One of the public facilities to be built is a garden. This study aimed to evaluate the condition of the soil layers and fertility for garden construction. The resistivity method determines the soil layer pattern using dipole configuration. Remote sensing methods are used to assess land suitability and soil fertility. Land suitability based on agro-climatic data soil fertility based on physical and chemical parameters is taken from SoilGrids 250 m. The results of the resistivity method showed various values between 1 – 110 Ωm, and there are three layers of soil up to a depth of 3.58 m The first layer is assumed to be silty clay (15 – 30 Ωm), the second layer is assumed to be clay (1 – 5 Ωm), and the third layer is assumed to be silty and sandy soil (70 – 110 Ωm). Based on the remote sensing data, the first layer had an ideal bulk density and cation exchange value, but the pH value and nitrogen content are less ideal. The second layer had an ideal value of cation exchange capacity and pH, a rather ideal bulk density value, and a low nitrogen content and is considered a fertile layer of soil. Keywords: Remote sensing, resistivity, soil fertility, soil layers, SoilGrids 250 m